Integration of control relations in the problematic of competition between regions - Olivier Crevoisier; Frédéric Quiquerez (European Regional Science Association (ERSA), 2004)
The aim of this paper is to integrate control relations in the analysis of regional production systems (RPSs). Financial economy aspects are often neglected in the analysis of classical and also regional economists. However, many studies show that this financial dimension is far from neutral and that it has a considerable impact on the real economy.During the twenty last years, Swiss regions have grown according to different rhythms, compromising the convergence process of per capita incomes. The approach in terms of RPSs used by Crevoisier, Corpataux and Thierstein (2001) explains a considerable part of these different evolutions. For the authors, the Swiss economy is made up of eleven RPSs strongly specialised in activities like chemistry, textile, microtechnic, tourism, administration and finance. The RPSs specialised in traditional activities have had poor performances while the financial systems has grown rapidly. The result of these different trajectories is a clear dualisation of the Swiss economy (Corpataux and Crevoisier, 2001). The RPS approach is mainly focused on endogenous phenomenons and considers that competitiveness of regions can be explained by the history of interactions between the actors and the institutions of the RPSs. In this paper, we propose to complete this approach by measuring the level of decision-making autonomy. In respect with the theory of spatial division of labour, the idea is to take into account the existence of multilocation firms or of groups, implying a distribution of the firm functions, but also a concentration of the strategic decisional power. In addition to that, we integrate another crucial aspect for the Swiss case, that is the fiscal federalism. In the opinion of Maillat and Quiquerez (2003), the fiscal competition explains a great part of the evolution of disparities. The great differences between regions' taxing rates clearly influences firm behaviour. Our main hypothesis is that the allocation of strategic establishments is not homogenous and that these headquarters are located in the RPS specialised in financial activities, reminiscent of what Sassen (1991) describes. But this situation is mitigated by the communities' fiscal competition. To show that, we use data on participations and on property of establishments. The aim is to measure the intensity of cross-regional relations and also to evaluate the autonomy degree of each RPSs. Results show that there are significant disparities in terms of control. Some regions are highly dependent of other: an important share of their economy is controlled by firms located in other regions. Financial centres are at the top of this hierarchy. Beside this domination, few cantons succeed in using the fiscal tool. The spatial division of labour approach and these results about control relations in RPSs complete the analysis done considering the Swiss regions specialisations. More than that, it reinforces the idea of a dualisation of the Swiss economy. Indeed, authors like Zimmerman (1995) and Dupuy and Gilly (1995) agree to say that the embededdness (anchorage) of non autonomous firms is precarious compared to independent SMEs. Concentration of strategic jobs, with highest wages, is a factor of regional divergence. This factor is reinforced by the weak embededdness (anchorage) of the secondary units, poorly implicated in the regional economic circuit and at risk of being partially or completely relocated. Moreover, and that will be the hypothesis for our next research, we think that possessions and subsidiaries finance the headquarters, breaking out the local accumulation networks. This situation may distort the competition between regions. Bibliography CORPATAUX J. et CREVOISIER O., 2001, « Place financière ou économie de production ? Les mécanismes de la dualisation économique et spatiale de la Suisse (1975-2000) », Géographie, Economie, Société, vol. 3, n°1, pp. 3-30. CREVOISIER O., CORPATAUX J. et THIERSTEIN A., 2001, Intégration monétaire et régions : des gagnants et des perdants, Paris, L'Harmattan. Dupuy C. et Gilly J.-P., 1995, « Les stratégies territoriales des grands groupes », in Rallet A. et Torre A. (éd.), Economie industrielle et économie spatiale, Economica, Paris. Maillat D. et Quiquerez F., 2003, « L'évolution des disparités régionales en Suisse », Contribution au XXXIXème colloque de l'ASRDLF : concentration et ségrégation, dynamiques et inscriptions territoriales, Lyon, 1-3 septembre. Sassen S., 1991, The global City : New York, London, Tokyo, Princeton University Press, Princeton. Zimmermann J.B., 1995, « Dynamiques industrielles: le paradoxe du local », in Rallet A. et Torre A. (éd.), Economie industrielle et économie spatiale, Economica, Paris.
Keywords: 330